158k views
16 votes
Please anyone I’ll mark as a branlist

Please anyone I’ll mark as a branlist-example-1
User BGorle
by
4.3k points

1 Answer

7 votes

Answer:

the first option is the answer, r = √6

Explanation:


hypotenuse = \sqrt{opposite {}^(2) + adjacent {}^(2) }

hypotenuse = q = √12

adjacent = p = √6

opposite = r

substitute the values into the hypotenuse formula


q = \sqrt{r {}^(2) + p {}^(2) }


√(12) = \sqrt{r {}^(2) + ( √(6) ) {}^(2) }


( √(12) ) {}^(2) = r {}^(2) +6


12 = r {}^(2) + 6


12 - 6 = r {}^(2)


6 = r {}^(2)


√(6) = r


r = √(6)

User Jason Fingar
by
4.8k points